DESAIN DAN ANALISIS WIND TURBINE PROTOTYPE TIPE PROPELLER POROS HORIZONTAL MENGGUNAKAN AIRFOIL AH79100 C BERBAHAN DASAR KOMPOSIT - Arif Budi Wicaksono; Risdiyono Risdiyono; Mohammad Farid Najmul Hilmi (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
The utilization of renewable energy at a low wind speed area (namely 2 m /s until 8 m / s) like Indonesia is still rarely performed due to it is low efficiency. This research is intended to know the performance of horizontal axis wind turbine propeller type 5-bladed, using airfoil AH79-100C type with 1,1 m it is diameter. It is expected which the parameters and characteristics of the blade can be used as reference to create a small-scale wind turbine. The results showed that the value of the power coefficient (Cp) is best obtained at a speed of 6 m / s with a value of 44,26%, while for the smallest power coefficient values obtained at wind speed of 17 m / s amounted to 16,76%. This wind turbine are most suitable for use at wind speeds ranging from 6 m / s to 12 m / s.